Effects of spray drying and ultrasonic assisted extraction on the phytochemicals, antioxidant and antimicrobial activities of strawberry fruit - Ashiq Hussain; Aneeqa Batool; Shazia Yaqub; Aqsa Iqbal; Samina Kauser; Muhammad Rehan Arif; Shafiqa Ali; Faiza Iftikhar Gorsi; Rizwan Nisar; Ashiq Hussain; Nida Firdous; Haya Fatima; et al. (Food Chemistry Advances)
Despite being nutrient-dense fruits with loads of bioactives, strawberries have a limited shelf life due to highly perishable nature. Therefore, to develop powders and extracts from these fruits through implementation of novel technologies is gaining importance. In current work strawberries pulp was dried through spray drying followed by ultrasonic assisted extraction using 70 % ethanol, to compare phytochemicals of fresh strawberries and strawberry powder. Both fresh strawberries and spray dried strawberry powder were found rich source of fiber, ash, protein and important minerals, however, strawberry powder presented significantly high fiber (4.72 %), ash (3.88 %) and protein (6.12 %). Total phenolic content (TPC), total flavonoid content (TFC), total carotenoid content (TC), DPPH free radical scavenging activity, total anthocyanins, vitamin C and β-carotene were found in significantly high amounts in ultrasonic assisted extracts of spray dried strawberry powder with values 480.18 mg GAE/100 g, 233.90 mg CE/100 g, 250.18 mg/100 g, 82.48 mg AAE/100 g, 8.04 mg/100 g, 32.16 mg/100 g and 92.03 mg/100 g, respectively. As compared to the ultrasonic assisted ethanolic extracts of fresh strawberries, the extracts of dried powder exhibited significantly high (p ≤ 0.05) antimicrobial activities. Thus, aforementioned techniques could prove useful for optimum retention of bioactives in strawberry powder.